Perkembangan Konsep Pendidikan dan Klasifikasi Pendidikan - Wardani Sihaloho; Risa Ummah Pratiwi; Intan Puspita Sari; Irma Qurata Aini; Zahra Yunita; Tiara Winanda (Jurnal Dirosah Islamiyah, 2023)
The purpose of this research is to find out the development of educational concepts and educational classifications. the concept of education can include the formation of attitudes and the development of basic skills which are all useful for realizing perfect human beings who are able to stand alone, are responsible and have the provisions to enter further education are also in line with views in education. The classification of education is divided into two, namely formal and non-formal education. This study uses a qualitative method. Education is a conscious effort made to direct someone from not knowing to knowing and changing one's mindset and attitude to be better. Education is very important in carrying out all activities carried out in life Keywords: Concept, Classification, Education.